Segregation distortion and linkage analysis in eggplant (Solanum melongena L.) - Barchi, Lorenzo; Lanteri, Sergio; Portis, Ezio; Stàgel, Anikò; Valè, Giampiero; Toppino, Laura; Rotino, Giuseppe Leonardo (Genome, 2010)
An anther-derived doubled haploid (DH) population and an F 2 mapping population were developed from an intraspecific hybrid between the eggplant breeding lines 305E40 and 67/3. The former incorporates an introgressed segment from Solanum aethiopicum Gilo Group carrying the gene Rfo-sa1, which confers resistance to Fusarium oxysporum ;; the latter is a selection from an intraspecific cross involving two conventional eggplant varieties and lacks Rfo-sa1. Initially, 28 AFLP primer combinations (PCs) were applied to a sample of 93 F 2 individuals and 93 DH individuals, from which 170 polymorphic AFLP fragments were identified. In the DH population, the segregation of 117 of these AFLPs as well as markers closely linked to Rfo-sa1 was substantially distorted, while in the F 2 population, segregation distortion was restricted to just 10 markers, and thus the latter was chosen for map development. A set of 141 F 2 individuals was genotyped with 73 AFLP PCs (generating 406 informative markers), 32 SSRs, 4 tomato RFLPs, and 3 CAPS markers linked to Rfo-sa1. This resulted in the assignment of 348 markers to 12 major linkage groups. The framework map covered 718.7 cM, comprising 238 markers (212 AFLPs, 22 SSRs, 1 RFLP, and the Rfo-sa1 CAPS). Marker order and inter-marker distances in this eggplant map were largely consistent with those reported in a recently published SSR-based map. From an eggplant breeding perspective, DH populations produced by anther culture appear to be subject to massive segregation distortion and thus may not be very efficient in capturing the full range of genetic variation present in the parental lines.